2018
DOI: 10.1155/2018/2312694
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Focuses Metalens for Copolarized and Cross-Polarized Transmission Waves

Abstract: Metasurfaces can reshape the wavefront in the desired manner by manipulating the phase profile and amplitude of the incident wave. In this paper, we demonstrate an ultrathin terahertz metalens based on our designed resonator structure, where the polarization state can be converted to the orthogonal direction and the parabolic phase profile is designed covering a 2 phase region. Many functional metalenses are also engineered to meet the demand of focusing, dual-polarization confocal, and dual focuses for orthog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The bifocal and multifocal lenses that can focus on different positions can be used in imaging systems [15,16], optical communication [17,18], and medical applications [19], etc. Previous studies have also used Pancharatnam-Berry (P-B) phase metasurface to achieve multi-focus focusing function [15,20].…”
Section: Introductionmentioning
confidence: 99%
“…The bifocal and multifocal lenses that can focus on different positions can be used in imaging systems [15,16], optical communication [17,18], and medical applications [19], etc. Previous studies have also used Pancharatnam-Berry (P-B) phase metasurface to achieve multi-focus focusing function [15,20].…”
Section: Introductionmentioning
confidence: 99%
“…Metalenses are the most promising optical elements that can replace or improve bulk optical systems. The recent research on broadband or tunable metalenses has led to increased interest of the metalenses. The advantages of their ultracompact properties have already been discussed in numerous applications, including mobile phone cameras, endoscopes, and ultrathin microscope objectives. In addition, their capability to manipulate a wavefront provides additional functionalities for various applications that cannot be realized in a traditional optical system or require a complex setup. In particular, metalenses making two focal spots in the longitudinal or transverse direction, called bifocal or dual-focus metalens, are promising building blocks for various applications, including optical communications, multi-imaging systems, , tomography technique, data storage, , and optical tweezers. In these applications, relative movement between the light beam and specimen is often required. For instance, one-dimensional nanoparticles, such as nanowires, which act as probes for high-resolution photonic force microscopy, should be stably trapped by dual focusing and displaced to measure a single-molecule force or scan a biological specimen. Fundamentally, this movement can be achieved by employing a specimen translation stage with a stationary light beam (stage scanning) or a scanned light beam with a stationary stage (beam scanning).…”
Section: Resultsmentioning
confidence: 99%
“…They have already been applied in many applications, particularly in metalenses 2,3 , holograms [4][5][6] , vortex beam generators [7][8][9] and so on. Metalenses with multi-foci are practically useful [10][11][12][13] due to their ultrathin configuration that can be integrated into miniature optical systems for multiple functions, and by far a group of multifocal metalenses have been reported [14][15][16][17][18][19][20] . Free control and continuous zooming of each foci from multifocal metalenses are of important use in realistic applications, and we propose a tunable bifocal metalens (TBML) in this study, with two continuous-zoom foci is proposed as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%